Living the Motto “Giving, Compassion, Self-Control”: Mindfulness Leadership in Practice - Barus, Rosnelly; Listyasari, Winda Dewi; Effendi, Mohammad Sofwan; Takdir, Muhammad; Mayasari , Linda Ika (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2025)
This study explores how mindfulness leadership is practiced within school “X” guided by the institutional motto “Giving, Compassion, Self-Control.” Using a qualitative narrative analysis design, the research investigates how mindfulness values are embedded in leadership and organizational culture. Data were gathered through in-depth interviews with the Head of School, supported by document analysis and field observations. The analysis reveals that mindfulness leadership extends beyond individual awareness to a collective ethos shaping relationships, communication, and decision-making. The leader models mindfulness through presence, emotional regulation, and compassionate discipline, cultivating a culture anchored in empathy, service, and reflective awareness. Barriers such as workload, time pressure, and maintaining consistency also emerge as challenges in sustaining mindful practices. Overall, the study illustrates how mindfulness leadership, when lived through shared institutional values, fosters a value-driven educational environment that nurtures both personal growth and organizational wellbeing.